Learning and policy improvement after disaster - Birkland, Thomas A. (2004)
This article considers whether policy makers in the aviation security field have learned from actual or apparent aviation security breaches in the late 1980s through 2001. The author finds that the loss of Pun Am Flight 103 in 1988 and of TWA Flight 800 in 1996 did lead to greater policy making attention to a relatively narrow range of issues raised by these events. The author also finds that the September 11 terrorist attacks led to a comprehensive search for improved policy tools to prevent a recurrence of the attacks. The author argues that this post-September 11 search would not have been possible without the debates on aviation safety that accompanied the earlier events. - Reproduced.
Keywords: Civil aviation